Designing English Reading Text Based on Bataknese Folklore - Br Sembiring, Yenita; Junita Vanesha Pinem; Saldy O. Simbolon; Yola Febriana (Cita konsultindo, 2022)
The low interest in reading students has an impact on the development of the world of science. Lack of interest in reading will also result in them being passive students in responding to lessons in class. Many students do not get used to reading because reading is considered a boring activity todo. To overcome this problem, the researcher aims to foster students' interest in reading through reading folklore texts. This type of research is qualitative descriptive where the results and discussion of the research occur naturally according to what is happening in the field. This research focuses on the folklore of North Sumatra, namely the Legend of Hanging Stone. The data for this study were taken from SMA N 1 DELITUA class of XI 30 students social major by asking them to read the story and after they finished reading, the researcher asked what moral values of life we can take from the legend. Based on the results of this study, it can be concluded that reading legend texts can increase the reading interest of each student.